Blackstone Building at the intersection of Hanover and Union Streets, ca. 1905 - Unknown (Tufts Archival Research Center, 2005)
Street-level view west of the Blackstone Building, located at the northwest corner of Hanover and Union Streets. Signage and awnings adorn the southeast and northeast elevations of the building, which face Hanover and Union Streets respectively. 140 Hanover Street is visible along the upper-right side of the photograph. The facades of (right to left) 128-118 Hanover Street, located to the southwest or left of the Blackstone Building, are visible near the left edge of the photograph. Street railroad tracks run down the center of Hanover Street. Commercial products are displayed in many of the buildings' storefront windows. Copyprint; former site of the First Baptist Church, 3rd ediface 6 3/8 x 7 9/16 Photographs